Pengaruh Komunikasi, Lingkungan Kerja dan Kompetensi Terhadap Kinerja Pegawai pada Kantor Bappeda Provinsi Sumatera Selatan - Anggun Permata Rohana; Baidowie Abdhie; Herman Efrizal; Rudy Chairudin (Equivalent : Journal of Economic, Accounting and Management, 2026)
This study basically aims to determine the influence of Communication, Work Environment, and Competence on Employee Performance at the BAPPEDA Office of South Sumatra Province. This research uses a quantitative approach, employing primary data collection techniques through the distribution of questionnaires and secondary data from the organizational structure. The study uses descriptive data analysis techniques, classical assumption tests, multiple linear regression analysis, and the statistical application SPSS version 26. The population consisted of 192 employees. Using the Slovin formula with a 10% error rate, the research sample amounted to 66 respondents. The results of the study indicate that Communication, Work Environment, and Competence simultaneously influence Employee Performance at the BAPPEDA Office of South Sumatra Province, with a significance value of F 0.000 < 0.05 and a multiple linear regression equation of Y = 11,011 + 0,150 X1 + 0,389 X2 + 0,247 X3. Partially, Communication has an effect on Employee Performance with a significance value of 0.038 < 0.05, the Work Environment has an effect with a significance value of 0.000 < 0.05, and Competence also affects Employee Performance with a significance value of 0.001 < 0.05. Abstrak  Penelitian ini pada dasarnya bertujuan untuk mengetahui pengaruh Komunikasi, Lingkungan Kerja dan Kompetensi Terhadap Kinerja Pegawai Pada Kantor BAPPEDA Provinsi Sumatera Selatan. penelitian ini menggunakan pedekatan kuantitatif, menggunakkan teknik pengumpulan data secara primer dengan penyebaran kuesioner dan data sekunder dari struktur organisasi. Penelitian ini menggunakan teknik analisis data deskriptif, asumsi klasik, analisis regresi linier berganda dan menggunakan aplikasi statistik SPSS versi 26. Adapun populasi berjumlah 192 dengan memakai rumus slovin dengan tingkat kesalahan 10% jadi sampel penelitian berjumlah 66. Hasil penelitian menunjukkan bahwa terdapat pengaruh Komunikasi, Lingkungan Kerja dan Kompetensi Terhadap Kinerja Pegawai pada kantor Bappeda Provinsi Sumatera Selatan, dengan nilai sig F 0,000 < 0,05 dengan persamaan  regresi  linier berganda  Y = 11,011 + 0,150 X1 + 0,389 X2 + 0,247 X3. Dan terdapat pengaruh Komunikasi secara parsial Terhadap Kinerja Pegawai dengan nilai sig 0,038 < 0,05, terdapat pengaruh Lingkungan Kerja dengan nilai sig 0,000 < 0,05, terdapat pengaruh Kompetensi Terhadap Kinerja Pegawai dengan nilai sig 0,001 < 0,05.